The student movement of Cordoba and its influence in Honduras - Murillo Lizardo, Orlando David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article aims to identify the consequences that the ideas of the Cordovan student movement had on the Republic of Honduras, the action of the political agenda of university students and its importance in the construction of the university in the twentieth century. The National Autonomous University of Honduras currently enjoys the exclusivity of governing the area of Honduran higher education, its foundations lie in the struggle flags of Honduran students for University Autonomy, University Reform, the social mission of the University, University co-government and student parity in the former University of Honduras. This research follows the historical perspective, through the collection and analysis of information based on the review of documents from primary and secondary sources.